2018
DOI: 10.3390/molecules23020456
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into σ1 Receptor Interactions with Opioid Ligands by Molecular Dynamics Simulations

Abstract: Despite considerable advances over the past years in understanding the mechanisms of action and the role of the σ1 receptor, several questions regarding this receptor remain unanswered. This receptor has been identified as a useful target for the treatment of a diverse range of diseases, from various central nervous system disorders to cancer. The recently solved issue of the crystal structure of the σ1 receptor has made elucidating the structure–activity relationship feasible. The interaction of seven represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The atomic motion and behavior of the compounds and their interactions with each other were studied by watching simulations' trajectories [43][44][45][46]. Our analyses showed that each of the active compounds in question was instantaneously attached to the NP (Fig.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 98%
“…The atomic motion and behavior of the compounds and their interactions with each other were studied by watching simulations' trajectories [43][44][45][46]. Our analyses showed that each of the active compounds in question was instantaneously attached to the NP (Fig.…”
Section: Molecular Dynamics Simulationmentioning
confidence: 98%
“…cocaine and methamphetamine) which are shown to interact with the σ 1 R. 14 This raises questions as to the possible involvement of the receptor in the pharmacological action or side-effects of these drugs. 4,5,16 On the other hand, this fact can also pave the way for interesting repurposing programmes. Novel σ 1 R ligands could be developed by structural optimization of known drugs (with some σ 1 R binding) aimed at increasing the σ 1 R affinity while decreasing the affinity for the original major target.…”
mentioning
confidence: 99%